Job tasks and the gender wage gap among college graduates - Todd R. Stinebrickner; Ralph Stinebrickner; Paul Sullivan (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2018)
Gender differences in current and past job tasks may be crucial for understanding the gender wage gap. We use novel task data to address well-known measurement concerns, including that standard task measures assume away within-occupation gender differences in tasks. We find that unique measures of task-specific experience, in particular high-skilled information experience, are of particular importance for understanding the substantial widening of the wage gap early in the career. Highlighting the importance of these measures, traditional work-related proxies for gender differences in human capital accumulation are not informative because general work experience is similar by gender for our recent graduates.
Keywords: 330